What is it about coral reefs? Translation of ecosystem goods and services relevant to people and their well‐being. Issue 8 (8th August 2021) - Santavy, Deborah L.; Horstmann, Christina L.; Sharpe, Leah M.; Yee, Susan H.; Ringold, Paul
Abstract: There is an astonishing diversity of ways in which people benefit from coral reefs. They provide recreation, resource extraction, inspirational, and educational opportunities, among many others as well as being valued just for their existence. As the condition of coral reef ecosystems decline, so do their ability to provide these benefits. Prudent management of coral reefs and the benefits they provide are important as some predict most coral reefs globally will be lost by the mid‐21st century. Meanwhile, coral reef managers have limited tools and relevant data to design and implement effective environmental management practices that will enable coral reefs to provide benefits demanded by society. We demonstrate an approach to identify and measure environmental components of coral reefs that directly benefit human well‐being. The approach views ecosystems through the lens of a specific set of beneficiaries and the biophysical features directly relevant to each. We call these biophysical features Final Ecosystem Goods and Services (FEGS). In our demonstration, we (1) identify a range of beneficiaries of coral reefs; (2) identify metrics of FEGS for those beneficiaries; and (3) describe how data quantifying those biophysical metrics might be used to facilitate greater economic and social understanding.